Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)
Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)
At the x-intercept on the graph of the equation, y=0. Take the equation, set 'y' equal to zero, and solve the equation for 'x'. The number you get is the x-intercept.
what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.
No. An equation must be equal to something, that's why its called an equation. 15x = 60 is an equation, in which case x equals 4
Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)
Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)
x=0
At the x-intercept on the graph of the equation, y=0. Take the equation, set 'y' equal to zero, and solve the equation for 'x'. The number you get is the x-intercept.
An equation may have zero, one, or more solutions (this is also true for a system of equations). The equation 2 + x = 5 has only solution, for example. x can only equal 3, so there is one solution. (An example of an equation with more that one solution is x2 = 4. In this case x can equal 2 or -2, so this equation has two solutions. An example of an equation with an infinite number of solutions is x + 6 = 3*2 + x. x can equal any number to make this equation true, so it has an infinite number of solutions. The equation x = x + 1 is an example of an equation with no solutions.)
523
28
what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.
Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.
3
Expressed as an equation, this would be equal to x - 7.
2 x 2 x 3 x 3